KEHIDUPAN SOSIAL EKONOMI MASYARAKAT NELAYAN DI KELURAHAN KARAN AUR KECAMATAN PARIAMAN TENGAH KOTA PERIAMAN (2000-2010) - Ayu, Intan Chindri; Nurhuda, Ahmad; Yulia, Refni (Pendidikan Sejarah, 2013)
ABSTRACTÂ The background of this research is to see the fishermen Karan Aur doing business in meeting the needs of family and economic life Economic life is limited so that the needs of fishing communities less accomplished family. The lives of the fishermen who are always categorized as poor. Based on this, the focus of the research problem posed was "How Social Life Aur Karan Economic Community 2000-2010 . Objective: To describe the socio-economic life of the fishing community in the Village of Karan Aur Pariaman 2000-2010. Historical research methods: (l) heuristic, (2) Kritik Sumber, (3) interpretation, (4) Historiography. Family needs of fishing communities have not been fulfilled bias, home form is still made of wood and thatch roofs, family lifestyle unmet by other electronic equipment as well as vehicles. Further education of children at the time of first fisherman has not done well, and even public health fishermen still treated to smart people. But with the help of the government can change the lives of fishermen in the fishing communities already met his family life, his lifestyle has undergone a change, education fishermen no longer drop out of school, health services are obtained from the fishermen community health centers services in Karan Aur.Â Keywords : Social, economic, fishing, lifestyle,Â